Protective effect of sialyllactose on the intestinal epithelium in weaned pigs upon enterotoxigenic Escherichia coli challenge. Issue 22 (21st October 2022) - Duan, Qiming; Yu, Bing; Huang, Zhiqing; Luo, Yuheng; Zheng, Ping; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun
Abstract : Sialyllactose (SL), one of the most abundant oligosaccharides present in porcine breast milk, has been implicated in many biological functions, including the prebiotic and immune-modulating effects. Abstract : Sialyllactose (SL), one of the most abundant oligosaccharides present in porcine breast milk, has been implicated in many biological functions, including the prebiotic and immune-modulating effects. This study was conducted to investigate the influences of dietary SL supplementation on intestinal barrier functions exposure to enterotoxigenic Escherichia coli (ETEC) in a porcine model. Thirty-two pigs were assigned to four treatments, fed with basal or SL-containing (5.0 g kg −1 ) diet, and orally infused with ETEC or culture medium. SL supplementation significantly reduced the diarrhea incidence and the abundance of E. coli in feces ( P < 0.05). Interestingly, SL attenuated ETEC-induced intestinal epithelium injury as indicated by the decreased serum concentrations of diamine oxidase (DAO) and d -lactate and reduced the number of apoptotic cells in the jejunal epithelium ( P < 0.05). Moreover, SL not only elevated the abundance of the tight-junction protein ZO-1 in the duodenal and ileal epithelium but also elevated the antioxidant capacity and the number of SIgA positive cells in the jejunal epithelium upon the ETEC challenge ( P < 0.05). Importantly, SL decreased the expression levels of inflammation-related genes such as the tumor necrosis factor-α ( TNF-α ), interleukin-6 ( IL-6 ), nuclear factor kappa-light-chain-enhancer of activated B cells ( NF-κB ), myeloid differentiation factor 88 ( MyD88 ) in the duodenum, and ileum upon ETEC challenge ( P < 0.05). SL also significantly elevated the expression levels of two critical antioxidant genes such as the nuclear factor erythroid-2 related factor 2 ( Nrf-2 ) and kelch-like ECH-associated protein 1 ( KEAP-1 ) in the jejunum ( P < 0.05). These results suggested that SL can alleviate ETEC-induced intestinal epithelium injury, which is associated with suppressed inflammation, improved intestinal immunity, antioxidant capacity, and improved intestinal epithelial functions.